Análisis a los estados financieros de la cooperativa de ahorro y crédito Cristo Rey en la ciudad de Loja. Períodos 2020-2021 - Samaniego Jiménez, Katherine Giomara (2023)
The Work of Curricular Integration Financial Analysis to the Cristo Rey Savings and Credit Cooperative in the City of Loja. Periods 2020-2021, it was developed in order to comply with the general and specific objectives that were raised, where the financial and economic situation was analyzed. In order to comply with the objectives, various techniques were implemented, such as the interview with the manager and the personnel in charge of the accounting area to obtain information in order to know the financial and economic situation of the cooperative through its financial statements for the periods 2020-2020. 2021. In the same way, methods such as the scientific method were applied, the same one that is in charge of collecting valuable information that is found in the theoretical framework, the methodology used was known and reviewing information contained in the financial statements that will be analyzed, the method analytical and mathematical was used in the vertical analysis where the financial and economic structure and the relevant value of each account will be extended, in the horizontal analysis the decrease or increase that each account has suffered was compared, in the same way the financial ones were applied considering the segment to which the cooperative belongs and finally the synthetic method where was able to publicize the results obtained from the Cooperative. Within the application of the vertical analysis, the degree of participation of each account was established, with its respective graphic representation and interpretation, determining that the assets as of 2021 are mainly made up of the credit portfolio with 80.55% participation has greater weight. consumer credit portfolio accounts to expire with 36.21% and microcredit portfolio accounts to expire with 48.50%; the same ones that are represent a medium level since they are focused within their service and line offered by the cooperative, the liabilities are made up of the most representative account that is obligations with the public represented by 68.58%, due to the fact that It is an entity in the financial sector, the equity with 26.78% which is adequate to support its current and future operations; The account with the highest representation within expenses corresponds to personnel expenses with 36.12% and in turn the public obligations account represented 31.53% finally of total income, interest and credit portfolio discounts represent 99.57% %. In addition, by carrying out the horizontal analysis, the variations that have occurred in 2021 with respect to 2020 were determined, it presented an increase in the credit portfolio of 21.01%; Obligations with the public increased by 14.91%, income increased by 49.05% and expenses decreased by 22.19%.